Isolation and biotyping of Salmonella and Escherichia coli associated with neonatal buffalo calves - Rana, N; Raut, A A; Khurana, S K; Manuja, A; Saini, A (The Indian Journal of Animal Sciences, 2012)
Diarrhoea is a predominant cause of mortality in neonatal buffalo calves leading to significant economic losses. Faecal samples from 149 neonatal buffalo calves were bacteriologically screened for Salmonella spp and Escherichia coli. Six isolates of Salmonella spp. could be recovered, out of which 4 belonged to Salmonella Infantis (6,7: r:1, 5), while one each belonged to Salmonella Gallinarum (1,9,12:-) and Salmonella Bareilly (6,7:y:1,5). Out of the 61 identified isolates of E. coli, 7 were rough (R), 1 was untypable (UT) and the rest 53 belonged to 35 different ‘O’ serogroups. Faecal recovery of E. coli belonging to O157 serogroup was not successful. In vitro drug sensitivity testing indicated gentamicin, norfloxacin and ciprofloxacin with respective sensitivities of 89.18%, 78.37% and 72.97% to be effective against E. coli. The isolates were, however, refractory to ampicillin, tetracycline and furazolidone. Isolation of multi-drug resistant coli warrants a careful selection of antibiotics for animal use from a public health perspective.